Policing rural and remote areas of Iceland : challenges and realities of working outside of the urban centres - Birta Dögg Svansd. Michelsen 1996- (2020)
With very few exceptions, factual and fictionalized the portrayals of the police and law enforcement are almost always situated in urban settings. Only ‘real’ police work occurs in the cities while policing in rural and remote areas is often depicted as less critical, or in some cases non-existent. In a similar fashion, much of the current academic literature has focused on police work in urban environments. It is only in the past five years that the academic focus has turned its attention to the experiences of police officers who live and work in rural and remote areas. To date, no such studies have yet examined the work of police officers in rural and remote areas of Iceland. This thesis forms a part of a larger scales, exploratory, qualitative study which examines the experiences of police officers who live and work in rural and remote districts of Iceland. Eight transcripts, from a total of twenty-three semi-structured, qualitative interviews, were selected randomly and subjected to thematic analysis. Four strong themes emerged from the data: Verbal Communication Skills, Emotional Labour, Dirty-Work and Boundaries between being on and off duty. This study found that all four of these aspects occur, in both urban and rural policing environments, however, they are magnified when the officers work alone, and with there being long all distances and time to the nearest back-up or support. Rural officers can rarely if ever, blend back into society when they end their duty, but rather remain on public display when both on and off duty in these non-urban areas. Nánast undantekningalaust hafa ímyndir lögreglu og löggæslu myndast með sjónarhorni beint að þéttbýlislögreglu. Þessar svokallaðar ímyndir ýta undir þann skáldskap að aðeins „raunverulegt“ lögreglustarf á sér stað innan þéttbýlis en ekki í dreifbýli, á meðan er löggæslan í dreifbýli og á afskekktum svæðum verður fyrir minni gagnrýni og jafnvel í sumum tilvikum engri. Að því sögðu hefur mikið af núverandi fræðiritum beinst að starfi lögreglu í þéttbýli. Á ...